Surface charge influences protein corona, cell uptake and biological effects of carbon dots. Issue 39 (28th September 2022) - Arezki, Yasmin; Delalande, François; Schaeffer-Reiss, Christine; Cianférani, Sarah; Rapp, Mickaël; Lebeau, Luc; Pons, Françoise; Ronzani, Carole
Abstract : In this first quantitative proteomic analysis of the protein corona formed on Carbon dots (CDs), we showed that protein corona identity is influenced by CD surface charge properties, which in turn impacts CD uptake and viability loss in macrophages. Abstract : Carbon dots are emerging nanoparticles (NPs) with tremendous applications, especially in the biomedical field. Herein is reported the first quantitative proteomic analysis of the protein corona formed on CDs with different surface charge properties. Four CDs were synthesized from citric acid and various amine group-containing passivation reagents, resulting in cationic NPs with increasing zeta (ζ)-potential and density of positive charges. After CD contact with serum, we show that protein corona identity is influenced by CD surface charge properties, which in turn impacts CD uptake and viability loss in macrophages. In particular, CDs with high ζ-potential (>+30 mV) and charge density (>2 μmol mg −1 ) are the most highly internalized, and their cell uptake is strongly correlated with a corona enriched in vitronectin, fibulin, fetuin, adiponectin and alpha-glycoprotein. On the contrary, CDs with a lower ζ-potential (+11 mV) and charge density (0.01 μmol mg −1 ) are poorly internalized, while having a corona with a very different protein signature characterized by a high abundance of apolipoproteins ( APOA1, APOB and APOC ), albumin and hemoglobin. These data illustrate how corona characterization may contribute to a better understanding of CD cellular fate and biological effects, and provide useful information for the development of CDs for biomedical applications.